Pengaruh Live Streaming Shopping di Tiktok terhadap Perilaku Impulsive Buying pada Generasi Z dengan Emotional Engagement sebagai Intervening - Sundari Sundari; Novemy Triyandari Nugroho (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
This study aims to determine the direct and indirect effects of the independent variables of live streaming interactivity, time constraints, and product demonstrations on impulsive buying in Generation Z, with emotional engagement as an intervening factor. The sample was obtained through purposive simple random sampling, involving 71 respondents from a population of 150. Data analysis was conducted using instrument quality testing, statistical tests, and path analysis. The results showed that the variables of time constraints and live streaming interactivity directly had a positive and significant effect on impulse buying. Product demonstrations had a negative direct effect. Emotional engagement mediated the influence of product demonstrations and time constraints. Conversely, emotional engagement did not mediate live streaming interactivity. Time constraints were the most effective and dominant variable in triggering impulse buying. R2 total = 0.7148, meaning that impulse buying can be explained by the variables of live streaming interactivity, time constraints, and product demonstrations, with emotional engagement intervening at 71.48%. The remaining 28.52% was explained by other variables.